2022
DOI: 10.3389/fbioe.2022.918032
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of the Reasonable Cervical Range of Motion to Prevent Non-Fusion Segmental Degeneration After Single-Level ACDF

Abstract: The compensatory increase in intervertebral range of motion (ROM) after cervical fusion can increase facet joint force (FJF) and intradiscal pressure (IDP) in non-fusion segments. Guiding the post-ACDF patient cervical exercise within a specific ROM (defined as reasonable ROM) to offset the increase in FJF and IDP may help prevent segmental degeneration. This study aimed to determine the reasonable total C0–C7 ROM without an increase in FJF and IDP in non-fusion segments after anterior cervical discectomy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…This study is based on the following hypothesis: With a decrease in total L1-S1 ROM, the ROM of each adjacent segment will decrease correspondingly, which can offset the increase in IDP and FJF after lumbar fusion [ 14 ]. Based on this hypothesis, a relative total L1-S1 ROM without an increase in IDP and FJF was proposed to guide the patients to conduct postoperative waist activities, which may help delay the progression of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…This study is based on the following hypothesis: With a decrease in total L1-S1 ROM, the ROM of each adjacent segment will decrease correspondingly, which can offset the increase in IDP and FJF after lumbar fusion [ 14 ]. Based on this hypothesis, a relative total L1-S1 ROM without an increase in IDP and FJF was proposed to guide the patients to conduct postoperative waist activities, which may help delay the progression of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous literature, an axial pressure of 75 N was applied to the upper surface of the C3 vertebra to mimic the weight of the head ( Zhang et al, 2022 ). A 1.0 Nm moment was loaded at the coupling point on the upper surface of the C3 vertebra to cause anterior flexion, posterior extension, lateral flexion, and axial rotational activity in the FE models ( Lee et al, 2016 ; Liang et al, 2022 ). The ROM of cervical spine surgical segments, the stress distribution of screws, plates, fusion devices, upper endplate, and intervertebral discs were recorded for each model and analyzed comparatively.…”
Section: Methodsmentioning
confidence: 99%
“…However, the current study aimed to provide a trend instead of natural status. Several recent studies have adopted similar methods in developing the finite element spine model and reported acceptable results (Wu et al, 2019;Liang et al, 2022;Zhang et al, 2022b). Third, the geometry of the human spine varies among individuals, while the model of this present study was developed on the basis of the data from a single patient.…”
Section: Osteogenesis Promotionmentioning
confidence: 99%